ACCOUNTING OF DAMPING IN THE EVALUATION AND SEISMIC STABILITY TASKS OF BUILDINGS AND STRUCTURES - K. V. Vorobieva; H. R. Zainalabidov; M. V. Frese (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
It is proved that for the majority of building structures characterized by different damping elements. The goal of constructing matrix hysteretic damping that takes into account the internal friction in the material. The study is based on generalized hypothesis of E. S. Sorokin on the proportionality of the matrices of damping and stiffness elements of the structure. The methods of accounting for damping in the evaluation of the earthquake resistance of structures. The exact and approximate methods of decomposition of the motion equations for the mode shapes are considered. It is established that the empirical criterion of the approximate method applicability of accounting for damping and its refinement on the basis of the initial approximation can serve as the correlation coefficients of waveforms. It is shown that for non-proportional damping it is possible to approximate the decomposition of movements according to oscillations forms of non-damped system, if the forms are weakly correlated.